2016
DOI: 10.1016/j.bmcl.2016.06.075
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antibacterial evaluation of macrocyclic diarylheptanoid derivatives

Abstract: Bacterial infections, caused by M. tuberculosis and other problematic bacterial pathogens, continue to pose a significant threat to global public health. As such, new chemotype antibacterial agents are desperately needed to fuel and strengthen the antibacterial drug discovery and development pipeline. As part of our antibacterial research program to develop natural product-inspired new antibacterial agents, here we report synthesis, antibacterial evaluation, and structure-activity relationship studies of an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…synthesized Cu–N 2 by leaching Cu–N/C in different acidic solutions, where Cu–N 2 and Cu–N 4 were obtained by leaching in H 2 SO 4 and HNO 3 , respectively. [ 51 ] This might be caused by different corrosive abilities between these acids. XANES shows that the valence state of Cu in Cu–N/C–H 2 SO 4 is between 0 and +1 by comparison with the reference spectra of Cu foil and Cu 2 O.…”
Section: Strategies To Tune the Surrounding Environment Of Atomic Metmentioning
confidence: 99%
See 1 more Smart Citation
“…synthesized Cu–N 2 by leaching Cu–N/C in different acidic solutions, where Cu–N 2 and Cu–N 4 were obtained by leaching in H 2 SO 4 and HNO 3 , respectively. [ 51 ] This might be caused by different corrosive abilities between these acids. XANES shows that the valence state of Cu in Cu–N/C–H 2 SO 4 is between 0 and +1 by comparison with the reference spectra of Cu foil and Cu 2 O.…”
Section: Strategies To Tune the Surrounding Environment Of Atomic Metmentioning
confidence: 99%
“…Another problem of ORR in energy conversion devices is the production of H 2 O 2 via the two‐electron pathway, which is harmful to energy efficiency and durability of the device. [ 48–50 ] Many methods have been developed to address this problem, [ 51–55 ] such as pore engineering, construction of heterostructures, and etc. Besides, the electrochemical H 2 O 2 synthesis via the two‐electron pathway has become a new research direction over recent years because of the great role of H 2 O 2 in environmental remediation [ 56–59 ] and as a promising clean fuel (for jet car and rockets, 60 wt% H 2 O 2 has an energy density of 3.0 MJ L −1 , higher than compressed H 2 gas at 35 MPa, 2.8 MJ L −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…3‐(4‐(Benzyloxy)‐3‐methoxyphenyl)‐prop‐2‐enal (11 b) : 1 H NMR (200 MHz, CDCl 3 ): δ =9.58 (d, J= 6 Hz, 1 H), 7.38–7.19 (m, 6 H), 7.04–6.99 (m, 2 H), 6.83 (d, J= 8 Hz, 1 H), 6.58–6.47 (m, 1 H), 5.14 (s, 2 H), 3.85 ppm (s, 3 H); 13 C NMR (50 MHz, CDCl 3 ): δ =193.5, 152.7, 151.1, 149.9, 136.3, 128.6, 128.1, 127.3, 127.2, 126.8, 123.2, 113.4, 110.4, 70.8, 56.0 ppm; MS (EI, 70 eV): m / z =268.1 (6), 91.1 (100), 65.0 (9); HRMS calcd for C 17 H 16 O 3 : 268.1099; found: 268.1097 (Δ=0.7).…”
Section: Methodsmentioning
confidence: 99%
“…Hao Lin's research group reported the structure-activity, route of synthesis, and antibacterial study of macrocyclic diarylheptanoids compound with the various amine, amide, urea, and sulfonamide functionalities in the extended pharmaceutical library. The outcome of their study produced macrocyclic geranylamine and 4-fluorophenethylamine substituted derivatives, which can be performed reasonable activity against M. tuberculosis and picked Gram-positive bacterial pathogens (Scheme 52) [129]. Bacterial contagion triggered by Mycobacterium tuberculosis (TB) and various problematic bacterial germ keep posing a vital threat to world public health.…”
Section: Medicinal Chemistrymentioning
confidence: 99%